Impact of pre‐existing interstitial lung abnormal shadow on lung injury development and severity in patients of non‐small cell lung cancer treated with osimertinib. (17th April 2022) - Shibaki, Ryota; Ozawa, Yuichi; Noguchi, Susumu; Murakami, Yusuke; Takase, Eri; Azuma, Yuichiro; Maebeya, Masaru; Sugimoto, Takeya; Hayata, Atsushi; Hayakawa, Takahiro; Tamaki, Shinya; Nakanishi, Masanori; et al.
Abstract: Background: First‐generation epidermal growth factor receptor‐tyrosine kinase inhibitor (EGFR‐TKI) sometimes causes lung injury, thereby affecting survival. Although pre‐existing interstitial lung abnormal shadow (pre‐ILS) increases the risk of lung injury by EGFR‐TKIs, its impact on osimertinib, a third‐generation EGFR‐TKI, remains unknown. Patients and Methods: This retrospective cohort study consecutively enrolled patients of EGFR‐ mutated non‐small cell lung cancer treated with osimertinib. Computed tomography images were obtained and evaluated independently by three pulmonologists in a blinded manner. Factors associated with lung injury were assessed using a logistic regression model. Survival curves were calculated by the Kaplan–Meier method and compared using a log‐rank test. Results: Of the 195 patients, 40 had pre‐ILS, and 21 (8 with and 13 without pre‐ILS) developed lung injury during the observation period. Multivariate analysis revealed that pre‐ILS was independently associated with lung injury (odds ratio, 3.1; 95% confidence interval [CI], 1.1–8.2; p  = 0.025). Severe (≥Grade 3) lung injury was observed in eight (4.1%) patients, of whom, two (5%) and six (3.9%) had and did not have pre‐ILS ( p  = 0.67), respectively. Grade 5 lung injury was not observed, and survival curves were similar between the patients who developed lung injury and those who did not (median 11 vs. 12 months; hazard ratio, 1.2; 95% CI, 0.56–2.7; p  = 0.60). Conclusions: Pre‐ILS increased the risk of lung injury in patients of non‐small cell lung cancer treated with osimertinib, while the severity of lung injury was not clearly affected by the presence of pre‐ILS. Abstract : Although pre‐existing interstitial lung abnormal (pre‐ILS) shadow has been known to be a risk factor of lung injury by EGFR‐TKIs, data on osimertinib are lacking. Current results demonstrated that pre‐ILS increases the risk of lung injury (odds ratio, 3.1; 95% confidence interval, 1.1–8.2; p  = 0.025) in the treatment with osimertinib. Notably, the incidence of grade ≥3 was similar between patients with and without pre‐ILS, which was 5% and 3.9%, respectively. The overall survival was similar for patients who developed lung injury and those who did not. However, we still need to be cautious during treatment with osimertinib in patients with pre‐ILS; further studies are warranted in this field.